A Study on Best Practice for Account Relationship Managers in Corporate and Commercial Banking - Loke, Carol Yih Chiew (2004)
With constant changes in the banking industry and rapid advance in technology and increasing competitiveness, more banks in Malaysia recognised that it could no longer rely on the traditional ways to deliver services to customers. Only through relationship management realignment can banks hope to counteract recent industry trends : declining profitability, lack of revenue growth and increased competition. Market leaders already have embarked on re-designing their relationship management approaches. In the context of corporate banking, the basic to business success today hence depends on the ability and delivery of value offerings and effective problem solving to create a competitive edge in account relationship management. In line with the growing competitiveness in the marketplace, timely implementation of practices by Account Relationship Managers (ARMs) such as real time financial planning, just-in-time customer response and demand driven customers require high degrees delivery of accuracy and confidence. Based on a detailed examination of literature reviews on relationship marketing, it was noted that there are endless researches done and empirical results on the area of relationship marketing. However, some of which are proving to be outdated due to today’s highly competitive global market. Many of which are on retail banking but there are only a handful on the area of corporate banking in respect of ARMs. As a result, the relevance of this study will aim to create more value added ideas and practices for implementation for the attention of the ARM in respect of Corporate and Commercial Banking departments.A qualitative approach by conducting interviews on 6 ARMs from both local and foreign banks in Malaysia was carried out with the aim to understand (1) the current Account Relationship Management for Corporate and/or Commercial banking; (2) current ARMs’ practices; (3) current Key Account Management and profitability analysis tools used by various ARMs and banks, and finally (4) to understand the training, development and reward system of ARMs from their respective banks. Based on the results from the research findings, some recommendations and tools to improve ARMs best practices, study limitations and directions for future researches are then discussed.